Business processes as business systems - Kaniški, Ivica (Array, 2018)
Business process is the foundation of the work organization of every business. It is a set of different activities or tasks that are carried out in a certain order and use certain resources of an organization with the aim of fulfilling the mission or the purpose of its existence. As each business process is defined by parameters such as output quality, speed, cost, added value and the like, it is logical that they are the cornerstone of achieving competitive advantage. It is therefore important to monitor and analyze them in order to remove any drawbacks in their performance before endangering the survival of a company. Business process is a structured, analytical, inter-functional set of activities that require continuous improvement. It represents a repetitive flow of activities with a clearly defined beginning and end, and in more or less constant intervals, creates value for the buyers.